1989
DOI: 10.1111/j.1365-2125.1989.tb03506.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the pharmacokinetics of levodopa administered alone and in the presence of carbidopa.

Abstract: 1. The effect of age on the pharmacokinetics of levodopa administered alone and in the presence of carbidopa was investigated in young and elderly healthy volunteers. 2. The plasma clearance of levodopa following intravenous administration of 50 mg was 14.2 +/‐ 2.8 (s.d.) ml min‐1 kg‐1 in the elderly compared with 23.4 +/‐ 4.1 ml min‐1 kg‐1 in the young (P less than 0.01) which resulted in a 49% greater area under the plasma concentration‐time curve (AUC) in the older subjects (P less than 0.01). The volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 30 publications
5
80
3
Order By: Relevance
“…However, there was no significant difference in GE between PD patients with severe and less severe disease, indicating that other factors than GE influence the levodopa uptake from the GI tract. It has earlier been shown that the absorption of levodopa from the gut is accelerated after long exposure to levodopa (180,181) and that age also seems to affect levodopa uptake since higher levels of levodopa has been seen in older PD patients (49,182). However, in our study neither significant age difference nor any obvious time difference of levodopa treatment was seen in the two PD groups.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, there was no significant difference in GE between PD patients with severe and less severe disease, indicating that other factors than GE influence the levodopa uptake from the GI tract. It has earlier been shown that the absorption of levodopa from the gut is accelerated after long exposure to levodopa (180,181) and that age also seems to affect levodopa uptake since higher levels of levodopa has been seen in older PD patients (49,182). However, in our study neither significant age difference nor any obvious time difference of levodopa treatment was seen in the two PD groups.…”
Section: Discussioncontrasting
confidence: 54%
“…the bioavailability was 30 % (22,35). By adding an AADC inhibitor (DDI) to every levodopa dose the levodopa available in plasma is increased by 35-80 % in human (35,49,(51)(52)(53)(54). It has been shown that the DDI carbidopa reduces this first-pass metabolism to less than 10 % of the dose absorbed (52).…”
Section: Levodopa In the Peripherymentioning
confidence: 99%
See 1 more Smart Citation
“…Levodopa has a short elimination half-life and stable concentrations are difficult to achieve with oral therapy. Multiple peaks commonly occur in the plasma concentration-time curve for levodopa following oral administration and further exaggerate the variability of plasma concentrations (Evans et al, 1981;Robertson et al, 1989;Wade et al, 1974). It has been suggested that these multiple peaks reflect the manner in which levodopa is delivered from the stomach to the site of carrier-mediated absorption in the small intestine (Evans et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent samples were withdrawn at the end of the infusion and 5, 10, 15, 30, 45, 60, 75, 90, 105, 120, 180, 240, 300, 360, 420 and 480 min after completion. Plasma was stored at -20°C until analysis as previously described [13].…”
Section: Methodsmentioning
confidence: 99%